Coordination Between Phloem Loading and Structure Maintains Carbon Transport Under Drought - Stanfield, Ryan C.; Bartlett, Megan K. (Frontiers in Plant Science, 2022)
Maintaining phloem transport under water stress is expected to be crucial to whole-plant drought tolerance, but the traits that benefit phloem function under drought are poorly understood. Nearly half of surveyed angiosperm species, including important crops, use sucrose transporter proteins to actively load sugar into the phloem. Plants can alter transporter abundance in response to stress, providing a potential mechanism for active-loading species to closely regulate phloem loading rates to avoid drought-induced reductions or failures in phloem transport. We developed an integrated xylem-phloem-stomatal model to test this hypothesis by quantifying the joint impacts of transporter kinetics, phloem anatomy, and plant water status on sucrose export to sinks. We parameterized the model with phloem hydraulic resistances and sucrose transporter kinetic parameters compiled from the literature, and simulated loading regulation by allowing loading rates to decline exponentially with phloem pressure to prevent excessive sucrose concentrations from inducing viscosity limitations. In the absence of loading regulation, where loading rates were independent of phloem pressure, most resistance values produced unrealistic phloem pressures owing to viscosity effects, even under well-watered conditions. Conversely, pressure-regulated loading helped to control viscosity buildup and improved export to sinks for both lower and higher resistant phloem pathways, while maintaining realistic phloem pressures. Regulation also allowed for rapid loading and export in wet conditions while maintaining export and viable phloem pressures during drought. Therefore, we expect feedbacks between phloem pressure and loading to be critical to carbon transport in active-loading species, especially under drought, and for transporter kinetics to be strongly coordinated with phloem architecture and plant water status. This work provides an important and underexplored physiological framework to understand the ecophysiology of phloem transport under drought and to enhance the genetic engineering of crop plants.